ASSESSMENT OF DEMAND FOR GRADUATES OF THE PROGRAMME «PUBLIC ADMINISTRATION - Ruslan A. Abramov; Natalya M. Zabaznova; Elena Yu. Khalatenkova (Moscow Polytechnic University, 2016)
In order to estimate the demand for graduates of the programme «Public administration» and find out what their professional self-fulfilment depends on, the authors have conducted an anonymous opinion survey of prestigious economic universities students (bachelor's and master's degree courses) and graduates specialized in this sphere. The questions were about the correspondence of the gained academic qualification and actual occupation, the importance of degree certificate, satisfaction with the education quality, attitude to different aspects of studying etc. Having organized the data and compared it with the previous surveys' results the authors came to a conclusion that such interdependent factors as forethought of career choice, students' vision of academic planning, approach to teaching, practice-oriented type of education are essential to professional success and application of knowledge and skills. Informants' answers helped to count out the percentage of graduates whose occupation is connected with public administration, to understand the reasons of choosing the relevant master course, to assess the significance of acquired competences and qualification for job placement at governmental organizations. The main scientific result of the survey is working out of a system of recommendations aimed at increasing demand for graduates specialized in the sphere of civil service, and, consequently, improving the efficiency of investment in management training. The presented measures could be used for the further modernization of the process of educational planning and could be taken into notice while developing academic programs.